THE IMPLEMENTATION OF DHIKR THERAPY TO REDUCE ANXIETY LEVELS IN ADOLESCENTS PREPARING FOR EXAMINATIONS - Kibtyah, Maryatul; Faidha Zahra, Aqila; Juniati, Riyani (Universitas Islam Negeri Mataram, 2024)
This article examines the influence of dhikr therapy in alleviating anxiety levels. Anxiety is characterized as a diffuse and pervasive sense of worry, often accompanied by feelings of uncertainty and helplessness. It manifests as an uncomfortable emotional state, frequently triggered by ambiguous or distressing experiences. Students, in particular, may encounter various forms of anxiety, such as situational anxiety during public presentations or generalized anxiety associated with academic evaluations. Anxiety is commonly identified through physical, behavioral, and cognitive symptoms. This study highlights the application of dhikr therapy as a calming intervention to mitigate anxiety. Employing a qualitative research method, the study adopts a literature review approach, drawing data from published sources, including academic articles and journals. Data collection involved systematic tracing of relevant literature. The findings indicate that dhikr therapy has a measurable effect in reducing anxiety levels, underscoring its potential as an effective therapeutic strategy.